Polyomavirus early-late switch is not regulated at the level of transcription initiation and is associated with changes in RNA processing. - Hyde-DeRuyscher, R (1988)
Polyoma gene expression is temporally regulated during productive infection of mouse cells. Early genes are expressed throughout the viral life cycle, but late mRNAs are not detected until after the onset of DNA replication. At late times, late-strand transcripts represent the great majority of viral-specific RNA in the cell. To learn more about the mechanism by which the early-late switch is regulated, we have carried out a detailed analysis of polyomavirus transcription in mouse NIH 3T6 cells. Nuclei were isolated from cells infected for 6, 12, 18, or 24 hr, and run-on assays were performed. The resulting RNAs were then hybridized to a number of immobilized early- and late-strand-specific probes, which represent the entire polyoma genome. Results indicate that the late promoter is always on, even in the absence of DNA replication. Even though the early-late switch is characterized by a greater than 300-fold difference in the ratio of steady-state early- and late-strand RNAs, there is only a 2-fold effect at the level of transcription initiation. Furthermore, the efficiency of termination for late transcripts is very high at early times during infection (greater than 90%) but drops drastically at late times (less than 40%). In other experiments, we have found an increase in splicing efficiency of late pre-mRNA molecules that parallels the decrease in termination efficiency. These results, taken together with other studies from our laboratory, have led us to propose two possible models for the temporal control of polyomavirus late gene expression.